Developing coaching expertise: Moving through the beginning-competent-proficient-expert continuum - Dieffenbach, K. (USA Triathlon Performance Coaching Newsletter)
Zum Entwicklungsweg des Trainers über die logischen Etappen Anfänger - kompetent - erfahren - Experte.